(untitled) (Research, Society and Development, 2022)
Plasma has a high concentration of platelets in a small final volume. Called Platelet Rich Plasma (PRP), it is considered a blood component that, when removed from the patient, can be used in the treatment of wounds both in humans and animals of various species, in order to obtain faster healing. Healing is a process resulting from the regeneration of damaged tissue, which occurs through a cascade of events that is divided into three phases: inflammation; proliferation and finally tissue remodeling. This work aimed to review the literature to better elucidate the efficacy of platelet-rich plasma gel in the treatment of dog wounds, through the healing response and tissue regeneration. A search was carried out for dissertations and scientific articles in Portuguese, Spanish and English, published between 1997 and 2019, in order to recognize the effects of platelet-rich plasma, its composition, method of preparation and use in wounds in animals, especially in dogs. It can be concluded that the treatment of wounds in dogs with plasma has a good antimicrobial effect, reducing the risk of infections, being easy to apply, resulting in good adherence to the wound area and a low cost of obtaining it.